The Fana' Concept of Abu Yazid al-Busthomi and Imam Junaid al-Baghdadi (Comparative Study) - Ahmad Nurkholis; Muhammad Valiyyul Haqq (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The concept of fana is a concept that developed in the third and fourth centuries hijriyah. A concept of fusion (trance) which later became an experience desired by many Sufism retainers. A Sufistic experience that must be passed and deliver Sufis at the top of the world of Sufism. with the experience that each Sufi feels so that many bring up various differences between one and another, then it also becomes a phenomenon for the fuqoha'. Abu Yazid al-Busthomi and Imam Junaid al-Baghdadi were one of the pioneers of the concept of Fana’. With a distinctly different background, between Sufi philosophy and Sunni. So the author takes the initiative and aims to combine the views between the two by examining a character who is balanced against and a character who has many adherents to this day, in order to get a good understanding and similarities or differences in the concept of Fana’'. This research uses library research, by means of qualitative analysis. As well as using primary and secondary sources. The results of this study are the concept of Fana’ must be together with the concept of Baqo’, awareness of a person's individuality has disappeared even though his physical form is still there. And to reach the peak of Fana’, the Salikin must leave the nature, character and personality as humans.